Disrupted H2S Signaling by Cigarette Smoking and Alcohol Drinking: Evidence from Cellular, Animal, and Clinical Studies - Ethan Read; Jiechun Zhu; Guangdong Yang (MDPI AG, 2021)
The role of endogenous hydrogen sulfide (H2S) as an antioxidant regulator has sparked interest in its function within inflammatory diseases. Cigarette and alcohol use are major causes of premature death, resulting from chronic oxidative stress and subsequent tissue damage. The activation of the Nrf2 antioxidant response by H2S suggests that this novel gasotransmitter may function to prevent or potentially reverse disease progression caused by cigarette smoking or alcohol use. The purpose of this study is to review the interrelationship between H2S signaling and cigarette smoking or alcohol drinking. Based on the databases of cellular, animal, and clinical studies from Pubmed using the keywords of H2S, smoking, and/or alcohol, this review article provides a comprehensive insight into disrupted H2S signaling by alcohol drinking and cigarette smoking-caused disorders. Major signaling and metabolic pathways involved in H2S-derived antioxidant and anti-inflammatory responses are further reviewed. H2S supplementation may prove to be an invaluable asset in treating or preventing diseases in those suffering from cigarette or alcohol addiction.